The Effects of Prosthetic Knee Joints in Walking and Dual-Task Activity Performance in Transfemoral Amputees: A Systematic Review - Amira Adlan, Nur; Arifin, Nooranida; Abu Osman, Noor Azuan (International Journal of Psychosocial Rehabilitation, 2019)
Objectives: The purpose of this systematic review is to study the effects of prosthetic knee joints in terms of temporal-spatial, kinetic, and kinematic assessment during walking and dual-task activity in transfemoral amputees. Methods: The search strategy was conducted based on five online databases: ScienceDirect, PubMed, Scopus, CINAHL, and Medline. A total of 19 articles were selected in this review. From the reviewed articles, a total of 635 participants took part in the studies, and the performance between transfemoral amputees, transtibial amputees, and healthy controls was analyzed. Fifteen reviewed articles were based on biomechanical gait assessment such as temporal-spatial, kinetic, and kinematics during walking. Another four reviewed articles studied the assessment of dual-task activity. Results: Patients with LEA, especially transfemoral amputees, have lower walking speed, stride length, and step time but with a greater step width, step time asymmetry, variability, and cadence compared to healthy controls. The amputees have a higher work rate, impulse, load rate, and force on intact sides. There were no significant changes in dual-task activity for both amputations except that there is a slight deterioration of performance in transfemoral amputees. Conclusion: Transfemoral amputees have difficulty gaining proper gait pattern and stability during walking and performing the dual-task activity. The higher k-level function indicates greater achievement in performing gait assessment and requires less cognitive attention. Further evaluation is needed, as dual-task gait assessment can help to improve gait rehabilitation among transfemoral amputees.